Implementasi Standar Nasional Pendidikan di Kabupaten Aceh Besar Suatu Persepsi dan Harapan Masyarakat - Alfi Syahril Fuadi Jaya; Ellyawati Ellyawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
This study aims to describe community perceptions and expectations of the Implementation of Eight Education Standards (1) content standards, (2) process standards, (3) graduate competency standards, (4) teaching staff standards, (5) standard facilities and infrastructure (6) management standards, (7) financing standards, and (8) assessment standards in Aceh Besar District. This research was conducted using descriptive methods, especially quantitative descriptive. Using questionnaire / questionnaire method, which is a method of data collection by using a questionnaire containing questions that are relevant to the purpose of the study. The results of the study illustrate that the application of national education standards in Aceh Besar which has been implemented so far has resulted in the perception of the community is very good